PENGARUH KOMPLEKSITAS AUDIT, LOCUS OF CONTROL, RISIKO KESALAHAN TERHADAP PENURUNAN KUALITAS AUDIT DENGAN PERILAKU DISFUNGSIONAL AUDITOR SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Kantor Akuntan Publik di Sumatera Bagian Tengah) - Pretty Sakta Riny; Emrinaldi Nur DP; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The trust of audited financial statement users to the public accounting profession relies on the quality audit report . Audit Quality is assessment of the process in conducting the audit tasks performed by an auditor thus generating an audit report are assessed based on factors that may effect the audit quality. The reduced audit quality behaviour can cause the low users confidence of audit report thus becoming a threat to the audit profession. The purpose of this research was to analyze the direct effect of the complexity of audit variable, locus of control and risk of error toward the reduce audit quality, and to examine the indirect effect between the complexity of audit, locus of control and risk of error to the reduce audit quality with auditors’ dysfunctional behavior as the intervening variable. The data collection of this research was using questionnaire method that distributed to 85 auditors working at Public Accounting Firm (KAP) in central Sumatra. The numbers of auditors who became research sample were 52 auditors from 17 public accounting firms. The collected data were analyzed by using Partial Least Square (PLS). 10 hypotheses are used for get the final research. It showed that the complexity of audit, locus of control, and risk of error affect the reduce of audit quality. This study showed that the complexity of audit and locus of control had effect toward dysfunctional behavior, whereas the risk of error variable did not have any effect toward the audit dysfunctional behavior.This study also showed that the dysfunctional behavior affect the reduce audit quality. When the independent and dependent variables were mediated by dysfunctional behavior, it showed that the complexity of audit, locus of control, and risk of error indirectly affected the reduce audit quality with auditors’ dysfunctional behavior as the intervening variable.Keywords: complexity of audit, locus of control, risk of error, reduce audit quality, and auditors’ dysfunctional behavior.